2003
DOI: 10.1590/s0036-46652003000600002
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic involvement in fatal human leptospirosis: clinical and histopathological features

Abstract: SUMMARYHyperamylasemia has been reported in more than 65% of patients with severe leptospirosis, and the true diagnosis of acute pancreatitis is complicated by the fact that renal failure can increase serum amylase levels. Based on these data we retrospectively analyzed the clinical and histopathological features of pancreas involvement in 13 cases of fatal human leptospirosis. The most common signs and symptoms presented at admission were fever, chills, vomiting, myalgia, dehydratation, abdominal pain and dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 29 publications
1
44
0
4
Order By: Relevance
“…This property of albumin is reported to be hindered by the high glucose concentration (Bourdon et al 1999). Glucose concentration is reported to increase in human leptospirosis with pancreatitis involvement (Daher et al 2003) this may have also been the case in this study but we have no data to confirm the involvement of pancreatitis. However, increased glucose in this study might have aggravated oxidative stress by inhibiting albumin's antioxidant activity (Bourdon et al 1999).…”
Section: Discussionmentioning
confidence: 51%
“…This property of albumin is reported to be hindered by the high glucose concentration (Bourdon et al 1999). Glucose concentration is reported to increase in human leptospirosis with pancreatitis involvement (Daher et al 2003) this may have also been the case in this study but we have no data to confirm the involvement of pancreatitis. However, increased glucose in this study might have aggravated oxidative stress by inhibiting albumin's antioxidant activity (Bourdon et al 1999).…”
Section: Discussionmentioning
confidence: 51%
“…2 Pancreatitis is described as an uncommon complication of leptospirosis, but there are a considerable number of reports in literature. [37][38][39][40] In the present study, the complications found were pulmonary bleeding (14%), tract intestinal bleeding (13%), atrial fibrillation (11.4%), pulmonary infection (6.0%), meningitis (1.0%) and pancreatitis (0.5%).…”
Section: Discussionmentioning
confidence: 68%
“…In the same time nonspecific inflammatory factors are involved. Hypovolemia, systemic vasculitis, leading to blood hyperviscosity, low-graded intravascular coagulation compromise the microcirculation, resulting in stasis and tissue hypoxia [2,4,5,6,9,14,16]. Perhaps immunological mechanisms play important role in the tissue injury [1,3,7,15,16].…”
Section: Doi: 105272/jimab200511113 Discussionmentioning
confidence: 99%
“…Hence functional pancreatic disorders prevalence in leptospirosis. They appears in immune phase of the disease [4].…”
Section: Doi: 105272/jimab200511113 Discussionmentioning
confidence: 99%